Environment-friendly electrolyte kit for electrolytic polishing of medical nickel-titanium alloy and use method thereof

CN123027641APending Publication Date: 2026-11-03NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202611384969.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing electrolytic polishing technology for nickel-titanium alloys suffers from problems such as strong acidity, high volatility, high toxicity, low dissolution efficiency, and difficulty in achieving both polishing efficiency and surface quality. In particular, when dealing with structures such as capillaries, filaments, and mesh supports, the costs of cleaning and waste liquid treatment are high, and excessively high local current density can lead to edge over-corrosion or pitting.

Method used

The solution employs a liquid-liquid dual-component design. Component A contains a premixed ethylene glycol solution of citric acid and glucose, while component B contains a premixed ethylene glycol-water solution of ammonium fluoride and triethanolamine. Through physical isolation during storage and transportation, the solution is mixed to form an electrolytic polishing working fluid. Citric acid provides an acidic environment, ammonium fluoride removes the film layer, glucose adsorbs and reduces local current, triethanolamine regulates interfacial dissolution, and ethylene glycol provides low volatility and conductivity. These components work synergistically to remove the film layer and level the surface of nickel-titanium alloys.

Benefits of technology

It achieves pre-configured stability of low-volatility and low-toxicity electrolyte, improves polishing efficiency and surface quality, shortens polishing time, reduces operational risks and waste liquid treatment costs, and ensures local current uniformity and edge protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123027641A_ABST
    Figure CN123027641A_ABST
Patent Text Reader

Abstract

The application discloses an environment-friendly electrolyte set for electrolytic polishing of medical nickel-titanium alloy, which comprises A agent and B agent which are physically isolated from each other, the A agent is a glycol premixed solution containing citric acid and glucose, and the B agent is a glycol-water premixed solution containing ammonium fluoride and triethanolamine; the volume ratio of the A agent to the B agent is 1: (0.5-2); and the application further discloses a use method of the environment-friendly electrolyte set for electrolytic polishing of medical nickel-titanium alloy. The environment-friendly electrolyte set is designed according to the characteristics of the medical nickel-titanium alloy, and the combination design of acidification and fluoride-containing sub-agent pre-dissolution, controlled acidification after mixing, and collaborative film formation in the anode diffusion layer enables the electrolyte to undertake the functions of acidification, film layer removal, interface adsorption, complexation leveling, solubilization oxidation and mass transfer control, and balance is achieved between the reaction rate, environmental protection, low toxicity and polishing effect, and the environment-friendly electrolyte set is suitable for the field of medical devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal surface treatment technology, and in particular relates to an environmentally friendly electrolyte kit for electrolytic polishing of medical nickel-titanium alloys and its application method. Background Technology

[0002] Nickel-titanium shape memory alloys are widely used in high-end implantable medical devices such as cardiovascular stents and guidewires due to their excellent superelasticity, shape memory effect, and good biocompatibility. However, after machining or laser cutting, nickel-titanium alloys often have microcracks, burrs, and heat-affected zones on their surfaces. Electropolishing is necessary to obtain a smooth surface, improving their corrosion resistance and fatigue life. Furthermore, the dense oxide film formed by electropolishing effectively reduces the nickel ion release rate, thus decreasing the sensitization potential of nickel-titanium alloy products.

[0003] Traditional electropolishing of titanium and nickel-titanium alloys often employs strong acid mixtures such as hydrofluoric acid + perchloric acid / sulfuric acid, or systems like sulfuric acid-methanol. For example, Chinese invention patent CN102899711B, "An Electropolishing Solution for Titanium and Titanium Alloys and an Electropolishing Process," discloses an electropolishing solution for titanium and titanium alloys composed of perchloric acid and acetic acid; Chinese invention patent CN105568357A, "A Continuous Electrochemical Polishing System for Nickel-Titanium Wires," discloses a sulfuric acid-methanol system for continuous electrochemical polishing of nickel-titanium wires; and Chinese invention patent CN1358240A, "An Electrolyte Composition for Electropolishing of Titanium and its Application Method," discloses a hydrofluoric acid-acetic acid system for electropolishing titanium. These systems typically suffer from high acidity, high volatility or toxicity risks, and stringent operational safety requirements. For structures such as capillaries, filaments, and mesh supports, the cleaning, detection, and waste treatment of residual electrolyte can increase process costs; strong acid systems may also cause excessively high local current densities at small protrusions or tips, resulting in edge over-corrosion or pitting.

[0004] In recent years, some environmentally friendly electrolytic polishing solutions have replaced some strong acids with salts. For example, Chinese invention patent CN101148774A, "A substrate pretreatment process suitable for anodizing of titanium and titanium alloys," discloses a pretreatment system for anodizing of titanium and titanium alloys containing lactic acid, but still contains perchloric acid or perchlorate; Chinese invention patent CN102312277B, "An electrolyte suitable for electrochemical polishing of titanium and titanium alloys and its application method," discloses an electrolyte formulation without strong acids, but uses formamide solvents; Chinese invention patent CN107460534B, "An electrochemical polishing liquid and polishing method for titanium and titanium alloys," discloses an electrochemical polishing system for titanium and titanium alloys containing sodium chloride, but still involves perchloric acid; Chinese invention patent CN109972193A, "A polishing liquid and method for electrolytic polishing of nickel-titanium alloy tubes," discloses an electrolytic polishing liquid and method for nickel-titanium alloy tubes in the sodium chloride-ethylene glycol direction, but the dissolution and mass transfer of salts in high-viscosity organic solvents may still be limited, thus affecting conductivity, dissolution rate, and polishing time.

[0005] Therefore, there is still a need for an electrolyte solution that is based on low-volatility solvents, is easy to pre-prepare and use, can improve the dissolution and electrolytic mass transfer of fluoride-containing salts, and also takes into account the surface smoothness and polishing efficiency of medical nickel-titanium alloys. Summary of the Invention

[0006] The purpose of this invention is to overcome the shortcomings of the prior art and provide an environmentally friendly electrolyte kit for electropolishing medical nickel-titanium alloys. This environmentally friendly electrolyte kit is designed specifically for the characteristics of medical nickel-titanium alloys. Through a combination of pre-dissolving acidic component A and fluorine-containing component B, controlled acidification after mixing, and synergistic film formation within the anodic diffusion layer, the electrolyte performs acidification, film removal, interfacial adsorption, complexation and leveling, solubilization and oxidation, and mass transfer control. It achieves a balance between reaction rate, environmental friendliness and low toxicity, and polishing effect, solving the problems of insufficient stability in pre-prepared electrolytes, slow dissolution of salts in ethylene glycol systems, operational risks posed by strong acids or volatile solvents, and the difficulty in simultaneously achieving polishing efficiency and surface quality in existing technologies.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is: an environmentally friendly electrolyte kit for electropolishing of medical nickel-titanium alloys, characterized in that it includes physically isolated agent A and agent B, wherein agent A is an ethylene glycol premixed solution containing citric acid and glucose, and agent B is an ethylene glycol-water premixed solution containing ammonium fluoride and triethanolamine; agent A and agent B are mixed at a volume ratio of 1:(0.5~2) to form an electropolishing working solution.

[0008] This invention addresses the problems of strong acidity, high volatility, high toxicity, and low dissolution efficiency in existing technologies by proposing an environmentally friendly electrolyte kit. It encapsulates a premixed solution of citric acid and glucose with premixed solutions of ammonium fluoride, triethanolamine, and a small amount of water, forming a liquid-liquid dual-agent structure with pre-dissolution and storage isolation. Ethylene glycol serves as the continuous phase, while a small amount of water improves the solubility and conductivity of fluoride-containing salts and provides weak oxidizing properties. Furthermore, the composition of each component is designed specifically for the characteristics of medical nickel-titanium alloys, creating a mass transfer environment different from the high-water-content citric acid-ammonium fluoride system. This allows the components to synergistically act on the medical nickel-titanium alloy for film removal, metal ion complexation, local current homogenization, and edge protection. The core design can be summarized into four mutually restrictive stages: (1) In the dispensing stage, salts that are difficult to dissolve quickly in ethylene glycol are pre-dissolved in water-containing agent B, and citric acid and glucose are pre-dissolved in ethylene glycol to obtain agent A; by controlling the volume ratio, the dynamic balance of acidified fluorine-containing species formed at the interface between citric acid and ammonium fluoride in the system is precisely preset at the moment of mixing; (2) In the storage and transportation stage, agents A and B are separated to avoid long-term direct contact between acidic components and fluorine-containing components; (3) In the use stage, the electropolishing working solution is obtained by mixing according to the designed volume ratio, so that low-concentration acidified fluorine-containing substances are dynamically formed in the mixed working solution; (4) In the electrolysis stage, fluoride is used to remove the surface film layer, citric acid complexes metal ions, glucose and triethanolamine are used to homogenize the interface current and local dissolution, a small amount of water provides weak oxidation, and ethylene glycol solvent is used to regulate the combination relationship of mass transfer and conductivity, so as to achieve high-quality electropolishing of medical nickel-titanium alloy; Specifically, citric acid in the electropolishing working solution provides an acidic environment and complexes the metal ions generated during anodic dissolution; ammonium fluoride provides fluoride ions to promote the removal of oxide or passivation layers on the nickel-titanium alloy surface and anodic dissolution, forming an F-containing oxide layer; glucose is adsorbed on the workpiece surface through its polyhydroxy structure, reducing local current concentration at protruding areas; triethanolamine regulates the dissolution state near the anode interface through complexation, adsorption, and buffering, improving surface smoothing and synergistically stabilizing the solution pH with citric acid; water is used to increase the dissolution rate of ammonium fluoride in the premix, increase ionic conductivity in the working solution, and provide weak oxidizing properties to form a weak anodic oxide film; ethylene glycol provides a low-volatility, high-viscosity continuous phase to regulate ion diffusion, bubble generation diffusion rate, and mass transfer rate near the workpiece surface.

[0009] The above-mentioned environmentally friendly electrolyte kit for electropolishing of medical nickel-titanium alloys is characterized in that the preparation method of agent B is as follows: ammonium fluoride is pre-dissolved in water, and then mixed with triethanolamine and ethylene glycol.

[0010] The present invention preferably uses agent A as a premixed solution with ethylene glycol as the main solvent. Citric acid and glucose are pre-dissolved before assembly, and ammonium fluoride is pre-dissolved in water before assembly. Then, it is mixed with triethanolamine and ethylene glycol to form agent B. By pre-dissolving the solid components separately, the dissolution time required to directly add ammonium fluoride to high-viscosity ethylene glycol at the application site is greatly reduced. By sealing citric acid and ammonium fluoride separately, direct contact between the two during storage and transportation is avoided to prevent the formation of acidified fluorine-containing species.

[0011] The above-mentioned environmentally friendly electrolyte kit for electropolishing medical nickel-titanium alloys is characterized in that the solute content in the electropolishing working solution is: citric acid 0.2mol / L~1.2mol / L, ammonium fluoride 0.5mol / L~1.5mol / L, glucose 5.0g / L~15.0g / L, and triethanolamine 5mL / L~15mL / L; the volume of deionized water accounts for 1%~10% of the total volume of the electropolishing working solution.

[0012] The reasons for designing the content range of each component in the electrolytic polishing working solution of this invention are as follows: In the ethylene glycol system, when the citric acid content is below 0.2 mol / L, the acidity adjustment and metal ion complexation ability are insufficient; when it is above 1.2 mol / L, it easily increases the risk of non-uniform corrosion and over-dissolution. When ammonium fluoride is below 0.5 mol / L, the surface film removal and conductivity are insufficient; when it is above 1.5 mol / L, it easily accelerates local dissolution and increases the load of fluoride-containing waste liquid. When glucose is below 5.0 g / L, the interfacial adsorption and brightening effect are not obvious; when it is above 15.0 g / L, it easily makes the system viscosity and organic matter load too high. When triethanolamine is below 5 mL / L, the leveling and complexation effects are insufficient; when it is above 15 mL / L, it easily causes over-complexation or changes the electrochemical response of the working solution. When water is below 1%, the improvement of ammonium fluoride dissolution and ion migration is not obvious; when it is above 10%, the system viscosity decreases, the local reaction rate increases, and the gas generation increases, which may increase the risk of edge over-corrosion.

[0013] The above-mentioned environmentally friendly electrolyte kit for electropolishing medical nickel-titanium alloys contains the following solutes in the electropolishing working solution: citric acid 0.3mol / L~0.6mol / L, ammonium fluoride 0.8mol / L~1.2mol / L, glucose 7.0g / L~11.0g / L, and triethanolamine 8mL / L~12mL / L; the volume of deionized water accounts for 3%~8% of the total volume of the electropolishing working solution.

[0014] The above-mentioned environmentally friendly electrolyte kit for electrolytic polishing of medical nickel-titanium alloys is characterized in that the solute content in agent A is: citric acid 0.4mol / L~2.4mol / L, glucose 10.0g / L~30.0g / L; the solute content in agent B is: ammonium fluoride 1.0mol / L~3.0mol / L, triethanolamine 10.0mL / L~30.0mL / L; and the volume of water accounts for 2%~25% of the total volume of agent B.

[0015] This invention also discloses a method for using an environmentally friendly electrolyte kit for electropolishing medical nickel-titanium alloys. The method is characterized by mixing and stirring agent A and agent B in a container separate from the polishing tank to obtain an electropolishing working solution. After transferring the electropolishing working solution to the polishing tank, the medical nickel-titanium alloy workpiece is connected to a DC power supply as the anode, and placed in the electropolishing working solution along with the cathode electrode for electropolishing.

[0016] The method described above is characterized in that the stirring time is not less than 3 minutes.

[0017] Compared with the prior art, the present invention has the following advantages: 1. This invention adopts a liquid-liquid dual-form design, pre-dissolving citric acid and glucose in agent A, and pre-dissolving ammonium fluoride and triethanolamine in agent B. Physical isolation reduces direct contact between acidic components and fluorine-containing components during storage, transportation and pre-preparation. When using, simply mix and stir according to the volume ratio to obtain the working solution, which helps to shorten the on-site solution preparation time and improve batch consistency.

[0018] 2. This invention uses ethylene glycol as the main low-volatility solvent and does not require the use of perchloric acid, methanol or hydrofluoric acid as separate formulation components in advance, which can reduce the need for on-site preparation of high-volatile organic compounds and high-strength acids.

[0019] 3. This invention is designed specifically for the characteristics of medical nickel-titanium alloys, F - In the citric acid system, Ni can participate in anodic dissolution, promoting the removal of the surface film. Citric acid can also timely complex and remove metal ions generated during anodic dissolution, avoiding excessive accumulation of local reaction products. The selective adsorption of glucose and the viscosity mass transfer control of ethylene glycol together reduce the instantaneous current concentration at the micro-protrusions. Triethanolamine further improves the uniformity of local dissolution through complexation and interfacial adsorption, while stabilizing the solution pH after reacting with citric acid. A small amount of deionized water improves salt dissolution, provides conductivity and weak oxidizing properties, but does not completely transform the system into a low-viscosity aqueous phase. The fluorinated acid species in the working solution are controlled by acidity, water content and electromigration, thus achieving a balance between reaction rate, leveling ability and edge protection.

[0020] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0021] Figure 1 This is a metallographic image of a medical nickel-titanium alloy workpiece before electropolishing in Embodiment 1 of the present invention.

[0022] Figure 2 This is a metallographic image of a medical nickel-titanium alloy workpiece after electrolytic polishing in Embodiment 1 of the present invention.

[0023] Figure 3 This is a scanning electron microscope image of a medical nickel-titanium alloy workpiece after electrolytic polishing in Embodiment 1 of the present invention.

[0024] Figure 4 This is an atomic force microscope image of a medical nickel-titanium alloy workpiece after electrolytic polishing in Embodiment 1 of the present invention.

[0025] Figure 5 This is a photograph of a medical nickel-titanium alloy workpiece after electrolytic polishing in Embodiment 1 of the present invention.

[0026] Figure 6 This is the full-spectrum XPS spectrum of the medical nickel-titanium alloy workpiece after electropolishing in Example 1 of the present invention.

[0027] Figure 7 This is the fine elemental XPS spectrum of the medical nickel-titanium alloy workpiece after electrolytic polishing in Embodiment 1 of the present invention.

[0028] Figure 8 This is a scanning electron microscope image of a medical nickel-titanium alloy workpiece after electrolytic polishing in Comparative Example 1 of the present invention.

[0029] Figure 9 This is an atomic force microscope image of the medical nickel-titanium alloy workpiece after electrolytic polishing in Comparative Example 1 of the present invention.

[0030] Figure 10 This is a photograph of the medical nickel-titanium alloy workpiece after electropolishing in Comparative Example 1 of the present invention.

[0031] Figure 11 This is a scanning electron microscope image of the medical nickel-titanium alloy workpiece after electropolishing in Comparative Example 2 of the present invention.

[0032] Figure 12 This is an atomic force microscope image of the medical nickel-titanium alloy workpiece after electropolishing in Comparative Example 2 of the present invention.

[0033] Figure 13 This is a photograph of the medical nickel-titanium alloy workpiece after electropolishing in Comparative Example 2 of the present invention.

[0034] Figure 14This is a scanning electron microscope image of the medical nickel-titanium alloy workpiece after electropolishing in Comparative Example 3 of the present invention.

[0035] Figure 15 This is a photograph of the medical nickel-titanium alloy workpiece after electropolishing in Comparative Example 3 of the present invention.

[0036] Figure 16 The image shows the scanning electron full spectrum (XPS) spectrum of the medical nickel-titanium alloy workpiece after electrolytic polishing in Comparative Example 3 of this invention.

[0037] Figure 17 This is the fine elemental XPS spectrum of the medical nickel-titanium alloy workpiece after electrolytic polishing in Comparative Example 3 of the present invention.

[0038] Figure 18 The image shows the metallographic structure of the medical nickel-titanium alloy workpiece after electrolytic polishing in Comparative Example 4 of this invention.

[0039] Figure 19 This is a photograph of the medical nickel-titanium alloy workpiece after electropolishing in Comparative Example 4 of the present invention. Detailed Implementation

[0040] Example 1 The environmentally friendly electrolyte kit of this embodiment includes physically isolated Agent A and Agent B. Agent A contains citric acid at a concentration of 0.8 mol / L and glucose at a concentration of 16.0 g / L; Agent B contains ammonium fluoride at a concentration of 2.0 mol / L and triethanolamine at a concentration of 20 mL / L, and the volume of deionized water accounts for 10% of the total volume of Agent B. The preparation method of Agent A is as follows: Take an appropriate amount of ethylene glycol, heat it to 40℃~60℃, add 0.4mol citric acid and 8.0g glucose in sequence, stir continuously until completely dissolved into a transparent viscous liquid, add ethylene glycol and make up to 0.5L, and seal in an individual package. The preparation method of Agent B is as follows: Measure 50 mL of deionized water, dissolve 1 mol of ammonium fluoride in the deionized water at 35 °C, stir for 5 min, then add 10 mL of triethanolamine, and finally add ethylene glycol and make up to 0.5 L. Stir until a clear fluoride-containing salt liquid is obtained (about 30 min), and seal it in an individual package. The method of using the environmentally friendly electrolyte kit is as follows: Pour agent A and agent B into the polishing tank at a volume ratio of 1:1, stir continuously at room temperature for 10 minutes to obtain the electropolishing working solution, and perform electropolishing on medical nickel-titanium alloy workpieces (voltage 25V, electrode spacing 25mm, polishing time 5min); The concentrations of each component in the electropolishing working solution are: citric acid 0.4mol / L, ammonium fluoride 1.0mol / L, glucose 8.0g / L, triethanolamine 10mL / L; the volume of deionized water accounts for 5% of the total volume of the electropolishing working solution.

[0041] In this embodiment, the metallographic image of the medical nickel-titanium alloy workpiece before electropolishing is as follows: Figure 1 As shown, the metallographic image, scanning electron microscope image, atomic force microscope image, and physical image of the medical nickel-titanium alloy workpiece after electropolishing are as follows: Figures 2-5 As shown, the microscopic surface of the medical nickel-titanium alloy workpiece after electropolishing is smooth, flat, and has extremely low roughness, while the macroscopic surface is bright and free of discoloration or thick oxide film. The full-spectrum XPS and fine-spectrum XPS of the medical nickel-titanium alloy workpiece after electropolishing are as follows: Figure 6 and Figure 7 As shown in the figure (characteristic peaks of each element or chemical component can be seen, such as KLL peak, LMM peak, 1s peak, and 2p peak), Ni and Ti elements both participated in the oxidation film formation process and formed a distinct F-containing film layer.

[0042] Comparative Example 1 The difference between this comparative example and Example 1 is that a 1.0 mol / L ammonium fluoride-ethylene glycol electrolytic polishing solution was used (the ammonium fluoride dissolution time is about 180 min).

[0043] This comparative example shows scanning electron microscope (SEM) images, atomic force microscope (AFM) images, and actual images of a medical-grade nickel-titanium alloy workpiece after electropolishing. Figures 8-10 As shown, compared with Example 1, the surface of the medical nickel-titanium alloy workpiece after electropolishing in this comparative example is significantly rougher, indicating that the electrolyte kit of the present invention can effectively improve the polishing quality and shorten the polishing time.

[0044] Comparative Example 2 The difference between this comparative example and Example 1 is that a 0.4 mol / L citric acid-ethylene glycol electrolytic polishing solution was used.

[0045] This comparative example shows scanning electron microscope (SEM) images, atomic force microscope (AFM) images, and actual images of a medical-grade nickel-titanium alloy workpiece after electropolishing. Figures 11-13 As shown, compared with Example 1, the surface of the medical nickel-titanium alloy workpiece after electropolishing is significantly rougher, indicating that the electrolyte kit of the present invention can effectively improve the polishing quality and shorten the polishing time.

[0046] Comparative Example 3 The difference between this comparative example and Example 1 is that a 1 mol / L sodium chloride-ethylene glycol electrolytic polishing solution was used (sodium chloride dissolution time was 360 min).

[0047] This comparative example includes scanning electron microscope images, physical images, XPS full spectrum and fine spectrum of a medical nickel-titanium alloy workpiece after electropolishing (characteristic peaks of each element or chemical component are visible in the images, such as KLL peak, LMM peak, 1s peak, and 2p peak). Figures 14-17As shown, compared with Example 1, the surface of the medical nickel-titanium alloy workpiece after electropolishing is significantly rougher, and the Ni element basically does not participate in the surface oxidation film formation, with elemental Ni being the main component. This indicates that the electrolyte kit of the present invention can effectively improve the polishing quality and shorten the polishing time.

[0048] Comparative Example 4 The difference between this comparative example and Example 1 is that it uses an aqueous electrolytic polishing solution of 1 mol / L ammonium fluoride and 0.4 mol / L citric acid-deionized water.

[0049] Metallographic images and physical photos of the medical-grade nickel-titanium alloy workpiece after electropolishing are shown in this comparative example. Figure 18 and Figure 19 As shown, compared with Example 1, the surface of the medical nickel-titanium alloy workpiece after electropolishing showed significant corrosion, and a large number of bubbles were generated during the polishing process, indicating that the electrolyte kit of the present invention can effectively improve the polishing quality and shorten the polishing time.

[0050] Example 2 The environmentally friendly electrolyte kit of this embodiment includes physically isolated Agent A and Agent B. Agent A contains 0.9 mol / L citric acid and 21.1 g / L glucose; Agent B contains 1.8 mol / L ammonium fluoride and 17.9 mL / L triethanolamine, and the volume of deionized water accounts for 4.5% of the total volume of Agent B. The preparation method of Agent A is as follows: Take an appropriate amount of ethylene glycol, heat it to 40℃~60℃, add 0.3mol citric acid and 7.0g glucose in sequence, stir continuously until completely dissolved into a transparent viscous liquid, add ethylene glycol and make up to 0.33L, and seal it in an individual package. The preparation method of Agent B is as follows: Measure 30 mL of deionized water, dissolve 1.2 mol of ammonium fluoride in the deionized water, dissolve in the deionized water at 40℃, stir for 5 min, then add 12 mL of triethanolamine, and finally add ethylene glycol and make up to 0.67 L. Stir until a clear fluoride-containing salt liquid is obtained (about 40 min), and seal it in an individual package. The method of using the environmentally friendly electrolyte kit is as follows: Pour agent A and agent B into the polishing tank at a volume ratio of 1:2, stir continuously at room temperature for 10 minutes to obtain the electropolishing working solution, and perform electropolishing on medical nickel-titanium alloy workpieces (voltage 25V, electrode spacing 25mm, polishing time 5min); The concentrations of each component in the electropolishing working solution are: citric acid 0.3mol / L, ammonium fluoride 1.2mol / L, glucose 7.0g / L, triethanolamine 12mL / L; the volume of deionized water accounts for 3% of the total volume of the electropolishing working solution.

[0051] Upon inspection, the surface of the medical nickel-titanium alloy workpiece after electropolishing in this embodiment is bright and free of discoloration or thick oxide film.

[0052] Example 3 The environmentally friendly electrolyte kit of this embodiment includes physically isolated Agent A and Agent B. Agent A contains citric acid at a concentration of 0.9 mol / L and glucose at a concentration of 16.4 g / L; Agent B contains ammonium fluoride at a concentration of 2.4 mol / L and triethanolamine at a concentration of 24.2 mL / L, and the volume of deionized water accounts for 24.2% of the total volume of Agent B. The preparation method of Agent A is as follows: Take an appropriate amount of ethylene glycol, heat it to 40℃~60℃, add 0.6mol citric acid and 11.0g glucose in sequence, stir continuously until completely dissolved into a transparent viscous liquid, add ethylene glycol and make up to 0.67L, and seal it in an individual package. The preparation method of Agent B is as follows: Measure 80 mL of deionized water, dissolve 0.8 mol of ammonium fluoride in the deionized water at 35°C, stir for 5 min, then add 8 mL of triethanolamine, and finally add ethylene glycol and make up to 0.33 L. Stir until a clear fluoride-containing salt liquid is obtained (about 30 min), and seal it in an individual package. The method of using the environmentally friendly electrolyte kit is as follows: Pour agent A and agent B into the polishing tank at a volume ratio of 1:0.5, stir continuously at room temperature for 10 minutes to obtain the electropolishing working solution, and perform electropolishing on medical nickel-titanium alloy workpieces (voltage 25V, electrode spacing 25mm, polishing time 5min); The concentrations of each component in the electropolishing working solution are: citric acid 0.6mol / L, ammonium fluoride 0.8mol / L, glucose 11.0g / L, triethanolamine 8mL / L; the volume of deionized water accounts for 8% of the total volume of the electropolishing working solution.

[0053] Upon inspection, the surface of the medical nickel-titanium alloy workpiece after electropolishing in this embodiment is bright and free of discoloration or thick oxide film.

[0054] Example 4 The difference between this embodiment and Example 1 is that: the concentration of citric acid in agent A is 0.4 mol / L, and the concentration of glucose is 10 g / L; the concentration of ammonium fluoride in agent B is 3.0 mol / L, and the concentration of triethanolamine is 30 mL / L; the volume of deionized water accounts for 20% of the total volume of agent B; and the volume ratio of agent A to agent B is 1:1. The concentrations of each component in the electropolishing working solution are: citric acid 0.2 mol / L, ammonium fluoride 1.5 mol / L, glucose 5.0 g / L, and triethanolamine 15 mL / L; the volume of deionized water accounts for 10% of the total volume of the electropolishing working solution. Agent A and Agent B are mixed to obtain an electropolishing working solution, which is then used for electropolishing of medical nickel-titanium alloy workpieces.

[0055] Upon inspection, the surface of the medical nickel-titanium alloy workpiece after electropolishing in this embodiment is bright and free of discoloration or thick oxide film.

[0056] Example 5 The difference between this embodiment and Embodiment 1 is that: the concentration of citric acid in Agent A is 2.4 mol / L, and the concentration of glucose is 30 g / L; the concentration of ammonium fluoride in Agent B is 1.0 mol / L, the concentration of triethanolamine is 10 mL / L, and the volume of deionized water accounts for 2% of the total volume of Agent B; the volume ratio of Agent A to Agent B is 1:1. The concentrations of each component in the electropolishing working solution are: citric acid 1.2 mol / L, ammonium fluoride 0.5 mol / L, glucose 15 g / L, and triethanolamine 5 mL / L; the volume of deionized water accounts for 1% of the total volume of the electropolishing working solution. Agent A and Agent B are mixed to obtain an electropolishing working solution, which is then used for electropolishing of medical nickel-titanium alloy workpieces.

[0057] Upon inspection, the surface of the medical nickel-titanium alloy workpiece after electropolishing in this embodiment is bright and free of discoloration or thick oxide film.

[0058] The above description is merely a preferred embodiment of the present invention and does not constitute any limitation on the present invention. Any simple modifications, alterations, or equivalent structural transformations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.

Claims

1. An environmentally friendly electrolyte kit for electrolytic polishing of medical nickel-titanium alloys, characterized in that, The solution comprises physically isolated Agent A and Agent B, wherein Agent A is an ethylene glycol premixed solution containing citric acid and glucose, and Agent B is an ethylene glycol-water premixed solution containing ammonium fluoride and triethanolamine; Agent A and Agent B are mixed at a volume ratio of 1:(0.5~2) to form an electropolishing working solution.

2. The environmentally friendly electrolyte kit for electrolytic polishing of medical nickel-titanium alloys according to claim 1, characterized in that, The preparation method of agent B is as follows: ammonium fluoride is pre-dissolved in water, and then mixed with triethanolamine and ethylene glycol.

3. The environmentally friendly electrolyte kit for electrolytic polishing of medical nickel-titanium alloys according to claim 1, characterized in that, The solute content in the electropolishing working solution is as follows: citric acid 0.2mol / L~1.2mol / L, ammonium fluoride 0.5mol / L~1.5mol / L, glucose 5.0g / L~15.0g / L, and triethanolamine 5mL / L~15mL / L; the volume of deionized water accounts for 1%~10% of the total volume of the electropolishing working solution.

4. The environmentally friendly electrolyte kit for electropolishing medical nickel-titanium alloys according to claim 3, wherein the solute content in the electropolishing working solution is: citric acid 0.3mol / L~0.6mol / L, ammonium fluoride 0.8mol / L~1.2mol / L, glucose 7.0g / L~11.0g / L, triethanolamine 8mL / L~12mL / L; and the volume of deionized water accounts for 3%~8% of the total volume of the electropolishing working solution.

5. The environmentally friendly electrolyte kit for electrolytic polishing of medical nickel-titanium alloys according to claim 1, characterized in that, The solute content in agent A is as follows: citric acid 0.4 mol / L~2.4 mol / L, glucose 10.0 g / L~30.0 g / L; the solute content in agent B is as follows: ammonium fluoride 1.0 mol / L~3.0 mol / L, triethanolamine 10.0 mL / L~30.0 mL / L; the volume of water accounts for 2%~25% of the total volume of agent B.

6. A method for using an environmentally friendly electrolyte kit for electropolishing medical nickel-titanium alloys as described in any one of claims 1 to 5, characterized in that, In a container separate from the polishing tank, agent A and agent B are mixed and stirred evenly to obtain an electrolytic polishing working solution. After the electrolytic polishing working solution is transferred to the polishing tank, the medical nickel-titanium alloy workpiece is connected to a DC power supply as the anode and placed together with the cathode electrode in the electrolytic polishing working solution to perform electrolytic polishing on the medical nickel-titanium alloy workpiece.

7. The method according to claim 6, characterized in that, The stirring time shall be no less than 3 minutes.

Citation Information

Patent Citations

  • Matrix pre-processing technique adapted for titanium or titanium alloy anode oxidation

    CN101148774A

  • Electrochemical polishing electrolyte adopted for titanium and titanium alloy, use method thereof

    CN102312277B

  • An electrolytic polishing solution for titanium and titanium alloys and an electrolytic polishing process

    CN102899711B

  • Nickel-titanium wire obtained through continuous electrochemical polishing

    CN105568357A

  • An electrochemical polishing slurry and polishing method for titanium and titanium alloys.

    CN107460534B